2015
DOI: 10.1007/s10493-015-9904-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and population dynamics of Ascidae, Blattisociidae and Melicharidae (Acari: Mesostigmata) in tropical flowers in Brazil

Abstract: Cultivation of tropical flowers has expanded considerably in Brazil, justifying efforts to determine the arthropods associated with it. Heliconia species are some of the most important tropical flowers in Brazil. Mites of the families Ascidae, Blattisociidae and Melicharidae are commonly found on those plants. They disperse from flower to flower on hummingbirds. The objective of this study was to identify the diversity of mites of this group in tropical flowers, with emphasis on Heliconia species, in Brazil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…nov., L. foliatisetus, L. gabrielae, L. jorgeamadoi, L. latinoamericanus, L. piracicabensis, and L. scutalis. The following 11 species were described from elsewhere and reported from Brazil in different studies, as shown in parentheses: L. barbensiensis (Britto et al 2015;Castro et al 2021), L. corticeus (Karg 1980), L. floridensis (Britto et al 2011(Britto et al , 2015Sourassou et al 2015), L. helvetius (Karg 1980;Mineiro et al 2009); L. humberti (Britto et al 2015); L. matthyssei (Britto et al 2015), L. meridionalis (present publication), L. nomus (Britto et al 2015), L. philippinus (Britto et al 2015), L. quinisetosus (Mineiro et al 2009) and L. subterraneus (Lawson-Balagbo et al 2007). Argolo et al (2018) presented a key for the separation of the Lasioseius species reported from Brazil.…”
Section: Lasioseius Species Reported From Brazil and Their Morphologi...mentioning
confidence: 99%
See 3 more Smart Citations
“…nov., L. foliatisetus, L. gabrielae, L. jorgeamadoi, L. latinoamericanus, L. piracicabensis, and L. scutalis. The following 11 species were described from elsewhere and reported from Brazil in different studies, as shown in parentheses: L. barbensiensis (Britto et al 2015;Castro et al 2021), L. corticeus (Karg 1980), L. floridensis (Britto et al 2011(Britto et al , 2015Sourassou et al 2015), L. helvetius (Karg 1980;Mineiro et al 2009); L. humberti (Britto et al 2015); L. matthyssei (Britto et al 2015), L. meridionalis (present publication), L. nomus (Britto et al 2015), L. philippinus (Britto et al 2015), L. quinisetosus (Mineiro et al 2009) and L. subterraneus (Lawson-Balagbo et al 2007). Argolo et al (2018) presented a key for the separation of the Lasioseius species reported from Brazil.…”
Section: Lasioseius Species Reported From Brazil and Their Morphologi...mentioning
confidence: 99%
“…The following 11 species were described from elsewhere and reported from Brazil in different studies, as shown in parentheses: L . barbensiensis (Britto et al . 2015; Castro et al .…”
Section: Lasioseius Species Reported From Brazil and Their Morphologi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the topic of pests and diseases were related to the incidence and severity in cultivation of heliconia caused by pathogens such as F. oxysporum f. sp. cubense, Pseudocercospora fijiensis; nematodes of the genus Meloidogyne, Helicotylenchus erythrinae, H. crenacauda, H. dihystera, Meloidogyne incognita, Pratylenchus zeae and Rotylenchulus reniformis, defoliators such as Cornops frenatum frenatum and mites, particularly specimens of Tropicoseius venezuelensis Baker & Yunker (Castro et al, 2008;Lemos et al, 2010;Sardinha et al, 2012;Sobrinho et al, 2012;Britto et al, 2015;Vázquez-Euán et al, 2019). Despite the affectations some authors recommend that the use of synthetic insecticides should be done only in extreme cases (Lemos et al, 2010).…”
Section: Productionmentioning
confidence: 99%